1998
DOI: 10.1046/j.1365-2265.1998.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of neoplasia in patients with pituitary adenomas

Abstract: We have demonstrated that the overall incidence of malignant tumours in patients with non-functioning pituitary adenomas and acromegaly is significantly higher than expected for general population and for our internal control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0
9

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(113 citation statements)
references
References 33 publications
2
102
0
9
Order By: Relevance
“…With the improvement in the management of acromegaly, more patients will reach ages at which cancer incidence increases, and it will be important in the future to compare results from acromegalic patients with those of age-matched populations. Colorectal cancer has been reported in about 1% of acromegalic patients, and prevalence in our population was similar (1.2%), as also were the prevalences of breast cancer (3.1%) and bronchial cancer (0.4%) (35)(36)(37)(38). Colonoscopic examinations were not carried out systematically in all patients in this observational registry, which explains the low prevalence of colon polyps identified (9.5%), in comparison with studies in which all patients underwent pancolonoscopy prospectively (9 -40%) (32).…”
Section: Morbiditymentioning
confidence: 72%
“…With the improvement in the management of acromegaly, more patients will reach ages at which cancer incidence increases, and it will be important in the future to compare results from acromegalic patients with those of age-matched populations. Colorectal cancer has been reported in about 1% of acromegalic patients, and prevalence in our population was similar (1.2%), as also were the prevalences of breast cancer (3.1%) and bronchial cancer (0.4%) (35)(36)(37)(38). Colonoscopic examinations were not carried out systematically in all patients in this observational registry, which explains the low prevalence of colon polyps identified (9.5%), in comparison with studies in which all patients underwent pancolonoscopy prospectively (9 -40%) (32).…”
Section: Morbiditymentioning
confidence: 72%
“…Some studies have shown a higher frequency of differentiated thyroid carcinomas in acromegalic patients (16,21,22) due to the increased level of GH and IGF-I. Calculated risk of thyroid cancer in these patients appears to be sixty-fold higher than in the overall population (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Bates et al observed an increased mortality from malignancies in hypopituitary women (44), whereas the risk of death in a malignant disease was unaffected in the prospective study by Tomlinson et al (47). In the retrospective study by Popovic et al, the rate of neoplasia in non-functional and GH-producing pituitary adenoma was compared with that in the general population (85). They found increased frequency of cancer both in patients with non-functional pituitary adenoma and in acromegalic patients as compared with the expected incidence in the general population (85).…”
Section: Risk Of Malignant Diseasementioning
confidence: 99%